Commentary: Thinking With Stories: Reconsidering Community Development Work (LEARNing Landscapes, 2016)
In the retelling of my experiences as a community development worker in Khao Lak, Thailand in 2004, I attend to possible shifts in community development practice through narrative pedagogy. In this moral space, I encounter the dominant community development story alongside the stories of displaced persons. Though this encounter I begin to retell the dominant community development story by thinking with stories, rather than about stories. It is here in the reconsideration that I wonder about the possibilities when one begins with the sacred stories of a sense of community as lived out in unfamiliar places.
Keywords: community; development; story